CRISIS MANAGEMENT CELL FOR MONITORING COVID-19 SITUATION IN PAKISTAN ARMED FORCES – A CASE STUDY - Bakht, Nausheen; Saleem, Salman; Nisar, Shazia; Zaidi, Syed Shahid Nafees; Mansoor, Eisha; Shahid, Syeda Aliza; Irshad, Shamim; Iqbal, Sana; Khan, Nazish (Pakistan Armed Forces Medical Journal, 2020)
'Reporting and monitoring systems cannot be hurriedly cobbled at the first sign of an impending emergency‟. Crisis Management Cell was established on 29 January 2020 as part of the Medical Directorate COVID-19 response strategy with a mandate to act as a data collection point & repository for relevant decision making andpolicy formulation. Since its inception, it has proved its mettleby enabling a paradigm shift from an existing traditional passive surveillance system to an active, near-real-time data collection and disseminationarrangement. This transition involved a whole-hearted commitment of top brass and a herculean effort on part of Crisis Management Cell. Its functioning non-stop,24/7 on war-like footings for attaining assigned objectives has beenhighly appreciated by all rank and file.By writing this case study, authorsintend to share theworkdone by Crisis Management Cell for nearly seven months. By narrating a tale of blood, sweat and tears thepurpose is to critically review the Crisis Management Cell structures, processes and outcomes. We provide insightful lessons and discerning tips based on our first-hand experience of what went well, what did not, and what could. The purpose is not only to highlightits distinctive work but also to highlight that the tasks were performed at break-neck pace. We conclude by commenting on theutility and effectiveness Crisis Management Cell in achieving the desired output which is also evident from the fact that itsinitial mandate pertaining to COVID-19 wasexpandedto include Dengue Surveillance and Disease Early Warning System.